Charge-modulated self-assembly and growth of conjugated polyelectrolyte-polyoxometalate hybrid networks. - SCHMITT, WOLFGANG; EVANS, RACHEL (My University, 2014)
Self-assembly of an anionic polyoxometalate with cationic conjugated polyelectrolytes leads to hybrid supramolecular networks whose dimensionality is controlled by the chain length and steric charge distribution.
PUBLISHED
Keywords: Chemistry; Nanoscience & Materials; Nanotechnology; New materials, supramolecular structures; Optical materials